2012
DOI: 10.1111/j.1440-1819.2011.02290.x
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐channel near‐infrared spectroscopy shows reduced activation in the prefrontal cortex during facial expression processing in pervasive developmental disorder

Abstract: Aim:  The purpose of the present study was to investigate whether individuals with pervasive developmental disorders (PDD) show differential activation during an emotional activation task compared with age‐ and sex‐matched controls, by measuring changes in the concentration of oxygenated (oxyHb) and deoxygenated (deoxyHb) hemoglobin, using near‐infrared spectroscopy (NIRS). Methods:  Fourteen patients with PDD and 14 age‐ and sex‐matched healthy controls participated in the study. The relative changes of conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 32 publications
2
6
0
Order By: Relevance
“…The students with presenteeism did not show significant increases in prefrontal cortex activation during the WFT and TMT tasks, whereas healthy controls did. Previous studies reported that healthy controls had a greater increase in oxy-Hb under various cognitive stimulations in prefrontal cortex compared to patients with depression [22] [23], schizophrenia [24], and pervasive developmental disorder [25] [26]. Our results are quite similar to these previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…The students with presenteeism did not show significant increases in prefrontal cortex activation during the WFT and TMT tasks, whereas healthy controls did. Previous studies reported that healthy controls had a greater increase in oxy-Hb under various cognitive stimulations in prefrontal cortex compared to patients with depression [22] [23], schizophrenia [24], and pervasive developmental disorder [25] [26]. Our results are quite similar to these previous studies.…”
Section: Discussionsupporting
confidence: 91%
“…This weaker response was related to more difficulty in recognising these expressions. The impairment was milder but qualitatively similar to the findings from the clinical group (Nakadoi et al, 2012), thereby supporting the existence of a broad autism spectrum.…”
Section: Introductionsupporting
confidence: 74%
“…NIRS measurements were performed as in our previous studies. 25 , 26 The 24 probes and four areas are shown in Figure 1 .…”
Section: Methodsmentioning
confidence: 99%